2009
DOI: 10.1002/gcc.20721
|View full text |Cite
|
Sign up to set email alerts
|

FAU regulates carboplatin resistance in ovarian cancer

Abstract: The development of chemotherapy resistance by cancer cells is complex, using different mechanisms and pathways. The gene FAU (Finkel-Biskis-Reilly murine sarcoma virus (FBR-MuSV)-associated ubiquitously expressed gene) was identified through functional expression cloning and previous data have shown that overexpression enhances apoptosis in several cell types. We demonstrate that the expression of FAU was reduced in the A2780cis (cisplatin resistant subclone of A2780) cell line compared with the A2780 ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Expression of fox increases the transforming capability and tumorigenicity of the virus, presumably by inactivating fau expression in the mouse (Michiels et al, 1993). Expression of fau is down-regulated in both breast cancer (Pickard et al, 2009) and ovarian cancer (Moss et al, 2010). A sequence antisense to fau is able to inhibit apoptosis (AP) induced by dexamethasone, UV or cisplatin in W7.2c cells (Mourtada-Maarabouni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of fox increases the transforming capability and tumorigenicity of the virus, presumably by inactivating fau expression in the mouse (Michiels et al, 1993). Expression of fau is down-regulated in both breast cancer (Pickard et al, 2009) and ovarian cancer (Moss et al, 2010). A sequence antisense to fau is able to inhibit apoptosis (AP) induced by dexamethasone, UV or cisplatin in W7.2c cells (Mourtada-Maarabouni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It can be further postulated that FUBI-mediated modification of Bcl-G forms part of the molecular mechanism by which FAU regulates apoptosis. Indeed, recent studies in our laboratory have shown that FAU gene expression is down-regulated in human breast, prostate and ovarian tumours [13][14][15] and that siRNA-mediated silencing of FAU and BCL-L14…”
Section: Introductionmentioning
confidence: 99%
“…Further work in human T-cell lines and the epithelial cell line, 293T/17, has confirmed that ectopic FAU expression increases basal apoptosis, and that siRNA-mediated silencing of FAU attenuates apoptosis in response to ultraviolet-C irradiation (Pickard et al, 2011). FAU also regulates apoptosis in other human epithelial cell lines derived from breast (Pickard et al, 2009), ovarian (Moss et al, 2010) and prostate tumours (see 'Implicated in'). FUBI has been shown to covalently modify Bcl-G (a pro-apoptotic member of the Bcl-2 family) in mouse cells (Nakamura and Tanigawa, 2003), and it is feasible therefore, that FAU regulates apoptosis via Bcl-G.…”
Section: Functionmentioning
confidence: 91%
“…Note A reduction in FAU gene expression has been reported for malignant versus normal ovarian tissue, and for Type I ovarian tumours (typically include mucinous, endometrioid, clear cell, and low-grade serous cancers), in particular (Moss et al, 2010). Over-expression of FAU in a cisplatin-resistant ovarian cancer cell subline, A2780cis, resulted in increased sensitivity to carboplatin-induced apoptosis (Moss et al, 2010).…”
Section: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation